Caso endoscópico - Pereira,Fernando (2011)
An eight-year-old boy, with Weaver Syndrome, was referred to the Gastroenterology Unit because of abdominal pain, more frequently localized to the right lower abdominal quadrant, weight loss and diarrhoea (without faecal mucus or blood) throughout the last three months. Slight macrocephly and pain on the right iliac fossa were the only abnormalities on physical examination. There was mild anemia, and elevation of globular sedimentation rate, protein C and orosomucoide. ASCA and faecal calprotectine were above the normal range. Upper endoscopy and colonoscopy were normal, and videocapsule enteroscopy showed lesions suggestive of Crohns disease of the ileum. The patient was treated with messalazine and became asymptomatic. Laboratory parameters were normal within two months.